2016
DOI: 10.1093/ehjci/jew134
|View full text |Cite
|
Sign up to set email alerts
|

Association of global and local low endothelial shear stress with high-risk plaque using intracoronary 3D optical coherence tomography: Introduction of ‘shear stress score’

Abstract: Local low ESS and expansive lumen remodelling are associated with HRP. Arteries with increased shear stress score have increased frequency of HRPs and propensity to present with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…In line with previous large studies, this study showed that the large plaque size at baseline was the most powerful predictor of increased plaque burden and worsening of clinically relevant luminal obstructions needing revascularization at follow-up. In a recently published cross-sectional study, optical coherence tomography (OCT)-derived CFD and plaque analysis was done in 30 patients with stable angina or ACS [51]. WSS was classified into low (≤25 th percentile), moderate (between 25th and 75th percentiles), and high (≥75 percentile) based on the distribution of WSS values in each artery.…”
Section: High Wall Shear Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous large studies, this study showed that the large plaque size at baseline was the most powerful predictor of increased plaque burden and worsening of clinically relevant luminal obstructions needing revascularization at follow-up. In a recently published cross-sectional study, optical coherence tomography (OCT)-derived CFD and plaque analysis was done in 30 patients with stable angina or ACS [51]. WSS was classified into low (≤25 th percentile), moderate (between 25th and 75th percentiles), and high (≥75 percentile) based on the distribution of WSS values in each artery.…”
Section: High Wall Shear Stressmentioning
confidence: 99%
“…), and endpoints [27,53]. Overall, it seems that the few studies [36,37,51] that failed to show an association between high WSS and high-risk plaques or showed an association between low WSS and features of high-risk plaques suffered from two common limitations: 1) dividing segments to only low and non-low WSS (no separation of high from normal/intermediate WSS) and/or 2) lack or limited number of segments with significant disease and therefore limited number of segments with high WSS. While the interplay between atherosclerotic plaque, artery, and WSS seems to be very dynamic and the exact mechanism of rapid plaque progression and triggers of expansive remodeling as well as the role of WSS in these processes is unclear, it is possible that both extremes of WSS (lower and higher than normal/physiologic WSS) are associated with high-risk plaque features at different phases of atherosclerotic plaque development.…”
Section: High Wall Shear Stressmentioning
confidence: 99%
“…Low fluid shear makes it easier for inflammatory cells such as leukocytes to initiate the inflammatory process. 26,27 High intramural stresses and strain stretch the cell gap junctions, enhancing inflammatory cells' infiltration into the vessel wall. 17,24,25 A previous simulation study on patient selection found that the prosthetic valve is especially beneficial for CVD CEAP clinical class 4e6 with significant reflux that enhances valve motion.…”
Section: The Role Of Solid Stresses On Mechanobiologymentioning
confidence: 99%
“…Clinical studies using computed tomography (CT) angiography, quantitative coronary angiography, and intravascular ultrasound have frequently detected atherosclerotic lesions at the bifurcation or curvature of coronary arteries 2 6 ) . Blood flow was found to be disturbed in these areas, and arterial wall shear stress was low and oscillated 5 , 7 ) . Seneviratne et al 8 ) reviewed the relationship between changes in arterial wall shear stress and plaque development and destabilization.…”
Section: Introductionmentioning
confidence: 98%